Effects of cuminaldehyde on toxins production of Staphylococcus aureus and its application in sauced beef. (July 2022) - Li, Hui; Huang, Yan-yan; Addo, Keren Agyekumwaa; Yu, Yi-gang; Xiao, Xing-long
Abstract: The inhibitory mechanism of CUM on Staphylococcus aureus exotoxins and invasive enzyme, and the effect of CUM on sauced beef were investigated. Treatment with sub-minimum inhibitory concentrations of CUM observed very little decrease in cell density after 24 h. Additionally, CUM reduced hemolytic activity by inhibiting the formation of heptamer, and inhibited the content of enterotoxin in culture medium and sauced beef. The transcription of genes encoding α-hemolysin, staphylococcal enterotoxin A and Panton-Valentine leukocidin were down-regulated after treatment with CUM. Compared with the control group, the addition of CUM caused a significant decrease in S. aureus counts, total volatile base nitrogen, acid value, and thiobarbituric acid reactive substances of sauced beef after 9 d. Furthermore, CUM improved the redness (a*) of sauced beef. These results confirmed that CUM could effectively restrain the synthesis of S. aureus toxin, and the addition of CUM to sauced beef was the potential way to inhibit the growth of food pathogens and maintain quality profiles. Highlights: Cuminaldehyde inhibited the production of staphylococcal exotoxins and invasive enzyme. CUM decreased the expression levels of sea, hla, hld, sarA, RNA III and lukS-PV. CUM delayed the growth of S. aureus and discoloration in sauced beef. CUM prevented the formation of total volatile base nitrogen, acid value, and thiobarbituric acid reactive substances in sauced beef.